Native language interference in learning english as a foreign language: an analysis of written material produced by spanish speaking students in senior high school classes. - Coello, Rafael (2009)
Language interference (also known as linguistic interference, cross-linguistic interference or transfer) is the effect of second language learners' first language on their production of the language they are learning. The effect can be on any aspect of language: grammar, vocabulary, accent, spelling and so on. It is most often discussed as a source of errors (negative transfer), although where the relevant feature of both languages is the same, it results in correct language production (positive transfer). The greater the differences between the two languages, the more negative the effects of interference are likely to be.